Використання соціальних мереж при отриманні вищої освіти в Україні - Яцух, Олег Васильович; Зоря, Михайло Віталійович; Yatsukh, Oleg; Zoria, Mykhailo (Запоріжжя : 2024, 2024)
UA: Як показали результати опитувань щодо використання молоддю (18-29 років) соціальних мереж, проведених громадянською мережею «ОПОРА», у 2022 році в Україні 73,8% молоді повідомили, що вони користувачі Telegram. Крім того, 98% молоді повідомили, що вони мають смартфон або доступ до нього, а 60% молоді заявили, що майже постійно знаходяться в Інтернеті. Що ще важливіше, вони стають усе більш використовуваними під час збройної агресії російської федерації проти України. Але оскільки молодь приділяє багато часу соцмережам, є сенс використовувати ці засоби і в освіті. У статті представлено досвід авторів щодо використання Telegram як засобу підтримки освіти, а головну увагу приділено результатам опитування, яке вивчало думки та ставлення студентів до Telegram у порівнянні з Moodle як нове явище в університетській освіті. EN: According to the results of surveys on the use of social networks by young people (18-29 years old) conducted by the civil network "OPORA", in 2022 in Ukraine, 73.8% of young people reported that they are users of Telegram. In addition, smartphone ownership has become a ubiquitous element of young people’s lives. Up to 98% of youth reported having or access to a smartphone, and 60% of youth reported being online almost all the time. More importantly, they are increasingly used during the armed aggression of the russian federation against Ukraine. But since young people spend a lot of time on social networks, it makes no sense not to use these tools in education as well. The article presents the authors’ experience of using Telegram as a means of supporting education, and the main attention is paid to the results of a survey that studied the opinions and attitudes of students towards Telegram in comparison with Moodle, as a new phenomenon in university education.
Use of social networks when receiving higher education in Ukraine
Keywords: використання соціальних мереж в освіті; Telegram; вища освіта; думки студентів про Telegram як засіб підтримки освіти; порівняння використання Telegram і Moodle в освіті; the use of social networks in education; higher education; students’ opinions about Telegram as a means of supporting education; a comparison of the use of Telegram and Moodle in education